Konsep Maslahah dan Mafsadah Menurut Imam Al-Ghazzali - Akbar Sarif; Ridzwan Ahmad (TSAQAFAH, 2017)
The concepts of maslahat and mafsadah known as the main reference in Islamic laws to resolve contemporary Muslims problems. The concepts of maslahat and mafsadah as a centre in maqâṣid al-syarî‘ah already discussed by Imam al-Ghazali in his books. Imam al-Ghazali well known to be the frst scholars in the study of these concepts. Imam al-Ghazali’s highlights the concepts of maslahat and mafsadah should be based on the texts (naṣṣ). However, Imam al-Ghazali mentioned the concept of maslahat used as a method not an absolute sources after al-Qur’an, al-Sunnah, ijmâ’ and qiyâs in the deriving of Islamic laws. This paper tries to explains the concepts of maslahat and mafsadah following the study conducted by Imam al-Ghazali. The fndings suggests that Imam al-Ghazali well known as the frst jurist who pioners the framework of maqâṣid al-syarî‘ah. There ara two reasons as to why he is considered as the pioneer of the concept of maqâṣid al-syarî‘ah. The frst reason is due to his systematic and detailed treatment of the concepts in his last and defnitive work on legal theory; al-Mustaṣfa. The second reason is due to the use of his terminologies and classifcations of the concept by later jurists. These all serve as the evidences to considering him as the pioneer of the concepts of maslahat and mafsadah as a legal theory. Moreover, Imam al-Ghazali tried to proposed several ‘tarjîḥ’ methods how to apply the both concepts when there is a contradiction between the two concepts.